2006
DOI: 10.1007/s00420-006-0106-7
|View full text |Cite
|
Sign up to set email alerts
|

8-Hydroxy-2′-deoxyguanosine as a marker of oxidative DNA damage related to occupational and environmental exposures

Abstract: Oxidative DNA damage is considered to play an important role in pathophysiological processes, ageing and cancer. So far major interest has been on measuring 8-hydroxy-2'-deoxyguanosine (8-OHdG), the preferred methods relying on HPLC or GC-mass spectrometry. The high biological relevance of 8-OHdG is due to its ability to induce G-->T transversions, which are among the most frequent somatic mutations found in human cancers. Effects of workplace exposures on the level of white blood cell 8-OHdG or urinary 8-OHdG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
204
1
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 298 publications
(228 citation statements)
references
References 110 publications
(124 reference statements)
11
204
1
5
Order By: Relevance
“…and non-smokers. Smoking has been consistently identified as a confounder for 8-oxodG, but various occupational studies did not reveal higher levels of 8-oxodG [24] in smokers as indicated by the present study. A study by Besarati Nia et al [25] reported that the level of 8-oxodG was consistently increased among smokers.…”
Section: Ijomeh 2013;26(5)contrasting
confidence: 74%
“…and non-smokers. Smoking has been consistently identified as a confounder for 8-oxodG, but various occupational studies did not reveal higher levels of 8-oxodG [24] in smokers as indicated by the present study. A study by Besarati Nia et al [25] reported that the level of 8-oxodG was consistently increased among smokers.…”
Section: Ijomeh 2013;26(5)contrasting
confidence: 74%
“…Although it is clear that several environmental exposures result in increased levels of 8-OxodG [49], the relation between levels of urinary 8-OxodG and future risk of health effects, such as cancer, is not well characterized. There is one Danish prospective study on 8-OxodG and lung cancer showing that increasing levels of 8oxodG…”
Section: Discussionmentioning
confidence: 99%
“…The 8-OxodG is the most frequent mutation in human cancers (33). Cooke et al (34) reported elevated concentrations of 8-oxodG in a high quantity of cases of several pre-cancerous and cancerous conditions.…”
Section: -Oxoguaninementioning
confidence: 99%